IMPLEMENTASI PEMBELAJARAN PAKET C DI PKBM BINA KARYA PADA KELOMPOK BELAJAR DESA TIBAWAN KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Nining Rianti Asih; Wilson '; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research program is PKBM package C including education equality. Educational equality package C is an alternative that people can not enroll in school. So that the implementation of learning C packages based learning National Education Ministerial Decree number 3 of 2008 and technical guidance package C 2016 PKBM Bina Karya. Formulation of the problem in this research is how the implementation of the package C based learning National Education Ministerial Decree number 3 of 2008 and technical guidance package C 2016 PKBM Bina Karya in the village study groups Tibawan Rokan IV Koto subdistrit Rokan Hulu distrit?. The purpose of this study was to determine the implementation of the package C based learning National Education Ministerial Decree number 3 of 2008 and technical guidance package C 2016 PKBM Bina Karya. This type of research is policy research with a qualitative approach. Informant in the study of 5 people, 1 informant core, 3 informant control, and 1 informant observers. Data collection instruments consisted of the researchers them selves and interview guide can sisted of 31 questions. Planning consists of data collection and selection of learners, the formation of study groups, collection dan selection of tutor and technical resorce persons, placement of learning and training, as well as inquiry operations of help. The implementation of learning begins with the fulfilment of a duty and the righ learners, tutors and resource technical, as well as a duty and the right organizers. For learning process and training in the form of learning academic and training skills. Evaluations that do is evaluation of and evaluation of the development of learners. It can be concluded planning is classified very well, because of 20 items 16 has been fulfilled. The Implementation of learning be categorized darn good because all has fulfilled. Evaluation be categorized good, because of 4 item only 2 who met.Key Words: Implementation, Learning Package C